Chapter Individual and social aspects of after-Covid-19 pandemic depression - Anselmi, Pasquale (Proceedings e report, 2023)
How did individual and social aspects influence depression feelings during the pandemic? In this paper, we analyse the data collected through a survey conducted in the second half of 2021 among a convenience sample of Italian adults. The survey was aimed at highlighting how Italians experienced the pandemic and the way they perceived their future. A total of 556 Italians answered the CAWI survey. The analyses of the collected data show that, while having been infected by the virus or having had a family member infected by it did not influence the depression level, other individual characteristics and subjective feelings did. In particular, being female, younger, having had low trust in information delivered by television, no experiences of smart working or remote learning, little support from friends and family, and being unable to imagine the future increased the likelihood to feel higher levels of depression. Being able to imagine the future mediated the relationships of age and smart working or remote learning experiences with depression. The results indicate that, having a lower ability to imagine the future, younger people and individuals who did not work or study remotely have also a greater tendency to feel depressed.